A pressure-state-response-support framework for assessing regional water environmental carrying status - Hu, Aqin; Li, Qingsheng (Frontiers in Environmental Science, 2022)
The water environment carrying status (WECS) is the embodiment of the ability of an aquatic ecosystem to maintain healthy and stable development; as such, it is an essential factor in the sustainable social and economic development of a region. To evaluate the water environment carrying status of a region, a new Pressure-State-Response-Support (PSRS) framework is proposed firstly. Secondly, a water carrying status index system containing 21 indicators is constructed based on this new model, and a water environment carrying status index (WECSI) is introduced to describe the water environment carrying status. Then, projection pursuit and entropy methods are used to calculate the water environment carrying status index of eight cities along the Yangtze River in Jiangsu province as examples. The results reveal that although the government has made substantial effort, the pressure subsystem is still dominated the changes of water environment carrying status, the eight cities still face significant pressure. The analysis indicated that government departments should commit to alleviating pressure and monitoring and supervising surface water quality while continuing to maintain a supporting force. The proposed framework and methodology is sound and effective for measuring the carrying status of regional water environment, and the methods can provide guidance for the Ecological Environment Department in ensuring the carrying capabilities of water environment and achieving sustainable development mission at regional level.